An Innovative Model for Creative Economy Development Based on Coastal Resource Potential: A Case Study in Bugis Village, Sape Subdistrict, Bima Regency - Arman, Arman; Jasman, Jasman (CV RIFAINSTITUT, 2025)
This study aims to critically explore the latent potentials and structural challenges inherent in the development of a creative economy grounded in coastal resource utilization in Bugis Village, Sape District, Bima Regency. Furthermore, it seeks to formulate an adaptive and sustainable development model designed to enhance local competitiveness. Anchored in a qualitative descriptive approach, this research captures the socio-economic dynamics and resource management strategies through triangulated data collection methods, including direct observation, in-depth interviews, and comprehensive document analysis. Research informants were purposively selected, encompassing village officials, fisheries entrepreneurs, and other key local stakeholders. Data analysis was conducted through a rigorous, multi-stage process involving data reduction, data display, and the drawing and verification of conclusions. Findings reveal that Bugis Village possesses a distinct comparative advantage in the fisheries sector, particularly through high-value commodities such as tuna, skipjack, mackerel, and Caulerpa seaweed. This potential is further bolstered by a strategic geographic location and the embedded local wisdom of traditional fishers in sustainably managing marine resources. Nevertheless, the advancement of the creative economy is impeded by multiple structural bottlenecks, including inadequate supporting infrastructure (e.g., cold storage facilities, post-harvest training), weak institutional coordination, and limited access to product innovation training and broader markets. The implications of these findings underscore the imperative to design a locally contextualized creative economy development model. Such a model should integrate institutional empowerment at the village level, continuous human resource capacity building, and collaborative multi-stakeholder engagement within a pentahelix framework. Key recommendations include the incorporation of a creative economy roadmap into village development planning and the establishment of a communication forum among economic actors to foster a synergistic, inclusive, and competitive creative economic ecosystem in coastal regions.